SLAP Lesion with Supraglenoid Labral Cyst causing Suprascapular Nerve Compression: A case report - Bryan Y Tan; Lee KT (Malaysian Orthopaedic Journal, 2012)
We present a case of left suprascapular nerve palsy in a 39-year-old female secondary to compression from a large ganglion cyst. She presented with a two month history of left posterior shoulder pain which affected her work and disturbed her sleep. Clinical examination revealed a positive O’Brien’s test. Supraspinatus and infraspinatus strength was mildly weakened. A magnetic resonance imaging (MRI) scan of the left shoulder revealed a superior labral anterior to posterior (SLAP) lesion with a large supraglenoid labral cyst extending posteriorly to the spinoglenoid notch, resulting in compression of the suprascapular nerve. Arthroscopy revealed the SLAP lesion with a haemorrhagic labral cyst at the posterosuperior aspect. Arthroscopic decompression of the cyst and SLAP repair with two suture anchors was performed. At 22 months postoperative follow-up, the patient’s left shoulder remained asymptomatic with full range of motion and full strength.